End-cap stabilized oligoynes: Model compounds for the linear sp carbon allotrope carbyne - Gibtner, Thomas; Hampel, Frank; Gisselbrecht, Jean-Paul; Hirsch, Andreas (Chemistry - A European Journal, 2002)
Three series of differently 3,5-disubstituted α,ω-diphenylpolyynes Ar-(C≡C)-Ar (n=2, 4, 6, 8, 10) were synthesized under optimized Cadiot - Chodkiewicz conditions, isolated and completely characterized. These compounds can be considered as model substances for the hypothetical one-dimensional carbon allotrope carbyne C. The longest sp-carbon chain contains 20 atoms and is therefore the longest, purely organic polyyne studied with NMR techniques. Extinction coefficients over 600 000 Mcm represent the highest measured quantitative values for that compound class so far. Comparisons with previous investigations and electrochemical studies allow the assignment of absorption for both wavelength regions structuring the UV/Vis spectra. Based on the trends in the spectroscopic behaviour of those molecules with increasing chain length, electronic as well as the NMR properties of carbyne are predicted, in line with our previously reported results. The observed stability properties promise the synthesis of even longer polyynes.